Determinants of Tanzanian Export Prices - Rollo, Valentina (World Bank, Washington, DC, 2013)
. This paper uses firm-level data to study the pricing-behavior of Tanzanian exporters. The important question of how exporting firms make pricing decisions has not received significant attention in the trade literature, which is more focused on factors that determine export flows. The results of the paper show that the free on board price of Tanzanian exports is differentiated both across exporters -- within product-destination pairs -- and across markets -- within firm-product pairs. Moreover, contrasting with existing evidence, price differentiation across destinations seems to be mainly relevant for homogenous goods. This result could indicate either that goods classified as homogeneous can potentially be differentiated by their intrinsic quality (such as coffee), or that firms charge different mark-ups in different markets. Although further work is needed to confirm what leads to price dispersion, allowing for the possibility that food products can be vertically differentiable amplifies the spectrum of existing opportunities for developing countries to exploit product differentiation and market niches. The study also discusses the implications of the empirical findings in light of the predictions of price and quality competition models, but finds that the results cannot be explained by a single trade model of quality or price competition.